2022
DOI: 10.1007/s00167-021-06847-7
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence in traumatic anterior shoulder dislocations increases the prevalence of Hill–Sachs and Bankart lesions: a systematic review and meta-analysis

Abstract: Purpose The extent of shoulder instability and the indication for surgery may be determined by the prevalence or size of associated lesions. However, a varying prevalence is reported and the actual values are therefore unclear. In addition, it is unclear whether these lesions are present after the first dislocation and whether or not these lesions increase in size after recurrence. The aim of this systematic review was (1) to determine the prevalence of lesions associated with traumatic anterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…Evaluating glenoid morphology may be valuable to determine shoulder instability and the need for surgery. Glenoid depth, version, inclination, the critical shoulder angle and smoking may be reliable predictors for instability [23,[29][30][31]. The alignment between the graft and glenoid curve may also predict outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluating glenoid morphology may be valuable to determine shoulder instability and the need for surgery. Glenoid depth, version, inclination, the critical shoulder angle and smoking may be reliable predictors for instability [23,[29][30][31]. The alignment between the graft and glenoid curve may also predict outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Bony lesions are common following anterior glenohumeral dislocation and may be present in up to 96% of patients [19,25,31]. Anterior glenoid bone loss can cause the shoulder 1 3 to be unstable in the mid-range of motion and Hill-Sachs lesions in the end range [2,9,14].…”
Section: Introductionmentioning
confidence: 99%
“…Glenohumeral joint dislocation accounts for more than 40% of joint dislocations in the whole body 3 , resulting in shoulder pain or dysfunction. It often occurs in young patients, with an average age of 20 years old, and more often in male patients than in female patients, the vast majority of which experience anterior dislocations (85%-95%) [4][5][6][7] . Unfortunately, this injury is associated with a very high rate of recurrence (85%) in younger athletes after the initial injury 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, primarily in the adult population, reported the prevalence of bony Bankart lesion to be between 0% and 43%, soft tissue Bankart between 20% and 100%, and Hill-Sachs lesion in 13% to 100% of shoulders with a traumatic anterior dislocation. 13…”
mentioning
confidence: 99%
“…Previous studies, primarily in the adult population, reported the prevalence of bony Bankart lesion to be between 0% and 43%, soft tissue Bankart between 20% and 100%, and Hill-Sachs lesion in 13% to 100% of shoulders with a traumatic anterior dislocation. 13 Lesions that occur less frequently than Bankart or Hill-Sachs injuries may still be present and result in recurrent instability. Identification of these lesions may require focused anticipatory examination of imaging studies, and recognition during surgical assessment is crucial to ensure adequate treatment and glenohumeral stabilization.…”
mentioning
confidence: 99%